Propaganda Zionis Yahudi dalam Film Animasi Despicable Me (Analisis Semiotik Simbol) - Ahmad Rofi; Nidaul Fitroh (El-Hikmah: Jurnal Ilmu Dakwah dan Komunikasi, 2016)
This study aims to determine the Zionist Jewish symbols in the animated film Despicable Me, as well as to know the meaning of these symbols. The research method uses a qualitative approach. The object of research are symbols of the Zionist Jews in the animated film Despicable Me. The data were analyzed using Sender Charles Peirce's semiotics by analyzing verbal and nonverbal symbols and icons on the analysis of the sign of the Zionist Jewish symbols in the film Despicable Me, in the form of tabulation and descriptive. Conclusion of the study, is diiperoleh 13 symbol consists of 2 symbols verbal and nonverbal symbols 11. All the symbols have the meanings connection with Jewish Zionist symbols.